Lanthanoid complexes of tetrazolyl-functionalised Calix[4]arenes - D'Alessio, Daniel Mark (Curtin University, 2015)
Syntheses of the bis-, tris- and tetra-tetrazolato calix[4]arene ligands were performed from their corresponding nitrile derivatives. Mono-nuclear lanthanoid complexes were characterised in the presence of triethylamine, while addition of aqueous ammonium acetate resulted in the formation of an unprecedented discrete linear nineteen lanthanoid hydroxo cluster (Ln19). It was found the length of the cluster could be altered to an Ln12 structure, while retaining an identical cluster motif, by simply replacing ammonium acetate with ammonium benzoate.